CO2 dissociation in a packed bed DBD reactor: effect of streamer discharge. (2nd June 2022) - Zhu, Min; Hu, Shengyu; Wu, Fangfang; Ma, Heng; Xie, Shenyi; Zhang, Chaohai
Abstract: Non-thermal plasma catalysis, as a special heterogeneous catalytic reaction, needs to consider both gas discharge and catalytic reaction. Packed bed dielectric barrier discharge (PB-DBD) is widely used in non-thermal plasma catalysis, but the exact control principle of gas discharge, especially streamer discharge, is not clear. In this study, therefore, the orderly arranged dielectric rods were packed in the discharge gap of PB-DBD, and the streamer discharge behaviors were controlled by adjusting their diameter(s), quantity(ies), location(s) and dielectric constant(s). Al2 O3 and ZrO2 dielectric rods with dielectric constants of about 9 and 25 were used as packing material. Pure CO2 was used as reaction gas and discharge gas. Discharge images showed that stable and controllable streamer discharges can be formed between the dielectric rod and ground electrode. The intensity, width and length of the streamer discharge can be significantly changed by optimizing the dielectric constant, diameter, packing number and position of the dielectric rod, thereby affecting the CO2 conversion efficiency. Increasing dielectric constant and the distance between the dielectric rod and ground electrode can increase the intensity of streamer discharge, thus promoting the CO2 conversion efficiency. Compared with an empty reactor, after packing 24 ZrO2 dielectric rods with a diameter of 1 mm, the CO2 conversion and energy efficiency increased from 9.58% to 20.1% and from 1.67% to 2.89%, respectively. In short, this research has important implications for plasma catalysis. This study not only reveals the synergistic characteristics between streamer discharge and CO2 dissociation, but also provides an important idea for structural optimization of PB-DBD catalyst.